Determination of Some Mineral Elements in Syrian Fresh Olive Fruits and Virgin Olive Oils Extracted From Wild and Cultivated Olive Fruits - Aziz Ramadan, Abdul; Mandil, Hasna; Shamseh, Rasha (Asian Journal of Chemistry, 2012)
Determination of some mineral elements (K, Mg, Na, Ca, Fe, Cu, Zn, Cr, Ni, Pb and Cd) in four varieties (Sorani, Zeiti, Qaisi and Jlot) of Syrian fresh olive fruits and virgin olive oils extracted from wild and cultivated olive fruits from three regions (Afrin, Raqqa and Horan) in Syria using flame and flameless atomic absorption spectrometry was studied. The limits of quantification were (expressed in mg kg-1 of dry weight) in fresh olive fruits 10460-15903, 264-497, 321-462, 209-329, 13.8-24.8, 5.4-9.9, 4.8-9.8, 1.5-3.0, 1.3-2.1, 0.015-0.042 and 0.012-0.023 for mentioned elements, respectively. The limits of quantification were (expressed in mg kg-1 of oil weight) in virgin olive oils extracted from wild and cultivated olive fruits 15.4-25.9, 3.70-5.42, 7.4-12.4, 22.4-42.8, 5.9-12.2, 0.78-1.38, 1.04-2.38, 0.062-0.152, 0.20-0.73, 0.010-0.029 and 0.001-0.014 for mentioned elements, respectively. In general, the mineral elements in virgin olive oils extracted from wild or cultivated olive fruits have increased in the oil extracted from olive fruits adjacent to the highway, but the Fe, Pb and Cd were more increase up to 2 times for Fe, 80 times for Cd and 140 times for Pb; making the samples of these oils are unfit for food according to CODEX alimentarius, No 33/2009 (FAO/WHO food standards). Finally, the fatty acids in the studied oils were identified. It was found that, the amount of linoleic acid rises when the temperature increases and the content of fruit's oil decreases, contrary to oleic acid.